2005
DOI: 10.1111/j.1398-9995.2005.00709.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin reactivity to aeroallergens is reduced in human T‐lymphotropic virus type I‐infected healthy blood‐donors (asymptomatic carriers)

Abstract: The HTLV-I infection reduces the frequency of respiratory allergy and skin reactivity to aeroallergens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Although we cannot rule out the possibility that the exacerbated Th1 immune response observed in HTLV-1 infection contributed to the decreased prevalence of atopy determined by the SPT, it is possible that other factors might be involved in reducing the skin test response to aeroallergens in HTLV-1-infected subjects. For instance, the response to the prick test with histamine, used as a positive control, was lower among HTLV-1 carriers (17). Interestingly, other investigators have also found that the test for delayed type hypersensitivity to antigens, a reaction associated with a type 1 immune response, also shows a decreased response by HTLV-1-infected subjects.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Although we cannot rule out the possibility that the exacerbated Th1 immune response observed in HTLV-1 infection contributed to the decreased prevalence of atopy determined by the SPT, it is possible that other factors might be involved in reducing the skin test response to aeroallergens in HTLV-1-infected subjects. For instance, the response to the prick test with histamine, used as a positive control, was lower among HTLV-1 carriers (17). Interestingly, other investigators have also found that the test for delayed type hypersensitivity to antigens, a reaction associated with a type 1 immune response, also shows a decreased response by HTLV-1-infected subjects.…”
Section: Discussionmentioning
confidence: 95%
“…We have previously published a case report regarding a patient who had severe asthma and HTLV-1 infection, but we later showed that the prevalence of atopy based on the positivity of SPT and clinical manifestations was lower in HTLV-1-infected subjects compared to uninfected controls (17,18). Although we cannot rule out the possibility that the exacerbated Th1 immune response observed in HTLV-1 infection contributed to the decreased prevalence of atopy determined by the SPT, it is possible that other factors might be involved in reducing the skin test response to aeroallergens in HTLV-1-infected subjects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations